2017
DOI: 10.3389/fmicb.2017.02069
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell Responses and Cytokine Profile in Intestines of Mice Infected with Trichinella spiralis

Abstract: The intestinal phase is critical for trichinellosis caused by Trichinella spiralis (T. spiralis), as it determines both process and consequences of the disease. Several previous studies have reported that T. spiralis induces the initial predominance of a Th1 response during the intestine stage and a subsequent predominance of a Th2 response during the muscle stage. In the present study, immune cells and cytokine profile were investigated in the intestine of mice infected with T. spiralis. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 38 publications
1
33
0
1
Order By: Relevance
“…A subset of T lymphocytes, the CD4+ T cells, plays a key role in parasitic infection and can polarize into Th1, Th2, Treg, and Th17 cells upon antigenic stimulation. T. spiralis and its secretory products can suppress inflammatory responses and induce Th2-type immune responses, as determined by the elevated Th2-associated cytokine levels observed in infected animals [17,18]. The Th1 phenotype immune response is induced during the intestinal stage and predominantly induces a Th2-type immune response during the ML phase [19].…”
Section: Introductionmentioning
confidence: 99%
“…A subset of T lymphocytes, the CD4+ T cells, plays a key role in parasitic infection and can polarize into Th1, Th2, Treg, and Th17 cells upon antigenic stimulation. T. spiralis and its secretory products can suppress inflammatory responses and induce Th2-type immune responses, as determined by the elevated Th2-associated cytokine levels observed in infected animals [17,18]. The Th1 phenotype immune response is induced during the intestinal stage and predominantly induces a Th2-type immune response during the ML phase [19].…”
Section: Introductionmentioning
confidence: 99%
“…IL-10 has a dual role in protective immune responses directed against the diverse life stages of T. spiralis parasites. IL-4 plays an important role as a positive regulator of intestinal mast cell responses and is involved in expelling intestinal adult worms in vivo (Ding et al, 2017). On the contrary, IL-10 has a negative effect on protecting newborn larvae, and the lack of IL-10 leads to improved immunity against NBL, as well as decreased numbers of ML cysts, which is associated with elevated IFN-γ (Helmby and Grencis, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the Th2 type immune response, in vitro studies have shown that helminth parasite antigens are capable of dendritic cells activating, inducing the synthesis of Th2 cytokines such as IL-4, IL-5, IL-10, and IL-13 [147,149,153,169]. Likewise, studies in in vivo models have shown that helminth parasites infection is a significant increase in the synthesis of IL-4, IL-5, IL-10, and IL-13 [150,151,159,170] (Figure 5). IL-10 may suppress antigen presentation by dendritic cells and inhibition of IL-12 secretion.…”
Section: Immune System Activation By Parasitic Helminth Infectionmentioning
confidence: 99%